Metronidazole and Vancomycin Have a Synergic Effect, with Plant Extracts as Helpful Tools to Combat Clostridioides difficile Infections - Nancy C. Ruiz-Pérez; Yuli Bayona-Pérez; Silvia Laura Guzmán-Gutiérrez; Ricardo Reyes-Chilpa; Víctor M. Luna-Pineda; Javier Torres; Mariana Romo-Castillo (Antibiotics)
Background/Objectives: The prolonged use of antibiotics is closely related to increased infections caused by Clostridioides difficile (Cdiff). Plant-origin compounds have been expanding in recent years as the best opportunity to identify new synergic therapies to combat antibiotic-associated diseases. Mexico has incredible plant biodiversity; natural compounds with antibacterial properties are an alternative treatment. The main objective of this study was to analyze the effect of medicinal plants with an antibacterial action against toxigenic clinical Cdiff strains that have a synergic effect on the antibiotics commonly used to combat this disease. Methods: The plants were selected for plants that were previously used in research, and their extracts were tested against Cdiff strains. The antibacterial activity, synergy, and antagonism between the extracts and their synergic effect with antibiotics were evaluated. Results: Our results demonstrated that some extracts have effective antimicrobial activity and synergic effects with vancomycin and metronidazole. Conclusions: This study suggests that plant extracts and plant compounds derived from these extracts could be used as synergic-antibiotic therapy to combat Cdiff infections.